Thin Film Processes - Artifacts on Surface Phenomena and Technological Facets 2017
DOI: 10.5772/66751
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thin Films of Sulfides of Cadmium, Lead and Copper by Chemical Bath Deposition

Abstract: The goal of this chapter is to present three kind of thin films for the materials, done by Chemical Bath Deposition technique, the materials are CdS, PbS and CuS. The characterization has been diversified, but consisting mainly X-ray Diffraction (XRD) giving hexagonal, cubic and amorphous structures of CdS, PbS and CuS respectively. The Raman dispersion let to found the characteristics peaks of vibration, one for the CdS located on 300.7 cm −1 , three for PbS and two more for the CuS. We use X-rays Photoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…35 It was observed that there was a slight decrease in the absorbance of Cu–S thin films at higher wavelengths, in accordance with the literature. 36 For low Cu concentrations, it was seen that the absorption increased as the Cu concentration increased. For low Sb concentrations, it was observed that the absorption decreased as the Sb concentration increased.…”
Section: Resultsmentioning
confidence: 98%
“…35 It was observed that there was a slight decrease in the absorbance of Cu–S thin films at higher wavelengths, in accordance with the literature. 36 For low Cu concentrations, it was seen that the absorption increased as the Cu concentration increased. For low Sb concentrations, it was observed that the absorption decreased as the Sb concentration increased.…”
Section: Resultsmentioning
confidence: 98%